IMPLEMENTATION OF THE SIDOARJO PEOPLE'S SERVICE SYSTEM APPLICATION (SIPRAJA) IN KLURAK VILLAGE, CANDI DISTRICT, SIDOARJO REGENCY - Rahmawati, Della; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of the Sidoarjo Public Service System (SIPRAJA) in Klurak Village, Candi District, Sidoarjo Regency, with a focus on evaluating its effectiveness in improving public service delivery. Method: A qualitative descriptive approach was employed, guided by Edward III’s policy implementation model, which emphasizes communication, resources, disposition, and bureaucratic structure. Results: The findings reveal that the Klurak Village Government has actively conducted socialization of the SIPRAJA application by involving community stakeholders to foster awareness and participation. Human resources and infrastructure have been adequately prepared, including adjustments to officer honorariums, while the bureaucratic structure supports service efficiency. Despite these strengths, challenges persist among residents with limited technological literacy, indicating the need for more comprehensive digital training. The Village Government demonstrates a positive disposition through transparent practices that aim to build public trust, supported by collaboration between village officials. Novelty: The study offers a comprehensive evaluation of SIPRAJA’s implementation at the village level by integrating communication strategies, resource allocation, and bureaucratic structures, highlighting the importance of targeted training to address digital literacy gaps and reinforcing the role of local governance in fostering transparent and participatory e-government practices.